Lowering Red Meat and Processed Meat Consumption With Environmental, Animal Welfare, and Health Arguments in Italy: An Online Experiment - Dijkstra, Arie; Rotelli, Valentina (Frontiers in Psychology, 2022)
Introduction. Besides being a source of valuable nutrients, meat consumption has various negative consequences; for the environment, for animal welfare, and for human health. To persuade people to lower their meat consumption, it is assumed that personal relevance of the topic lowering meat consumption is important, as it determines how people perceive the quality of the arguments. Method. In an experimental field study (N=139), participants recruited from the general population were randomized to one of four conditions with text with pictures on the environmental, the animal welfare, or the health consequences of meat consumption, or a text on mustard (the control condition). The dependent variables were self-reported red meat and processed meat consumption after two weeks. Personal relevance was assessed at pre-test with self-reported meat consumption and intention. Results. The interaction between pre-test meat consumption and condition was significant: In participants who scored high on pre-test meat consumption, the self-reported red meat consumption after two weeks in the health argument condition was significantly lower compared to the control condition and the environmental argument condition. The effects of pre-test intention as a moderator were less certain. Discussion. The persuasive effects of the different arguments only made a difference in people who ate a relatively high level of meat at pre-test, and the type of arguments was of importance. Although the present outcomes are caused by the specific formulations of the arguments in this study, the results do show that it is relevant to carefully choose the arguments to assure effectiveness.